Orange-Reddish Light Emitting Phosphor GdVO4:Sm3+ Prepared by Solution Combustion Synthesis - M. S. Rabasovic; J. Krizan; S. Savic-Sevic; M. Mitric; M. D. Rabasovic; B. P. Marinkovic; D. Sevic (Journal of Spectroscopy)
The gadolinium vanadate doped with samarium (GdVO4:Sm3+) nanopowder was prepared by the solution combustion synthesis (SCS) method. After synthesis, in order to achieve the full crystallinity, the material was annealed in air atmosphere at 900°C. Phase identification in the postannealed powder samples was performed by X-ray diffraction, and morphology was investigated by high-resolution scanning electron microscopy (SEM). Photoluminescence characterization of the emission spectrum and time-resolved analysis have been performed using the tunable laser optical parametric oscillator excitation and the streak camera. Several strong emission bands in the Sm3+ emission spectrum were observed, located at 567 nm (4G5/2–6H5/2), 604 nm (4G5/2–6H7/2), and 646 (654) nm (4G5/2–6H9/2), respectively. The weak emission bands at 533 nm (4F3/2–6H5/2) and 706 nm (4G5/2–6H11/2) and a weak broad luminescence emission band of VO43− were also observed by the detection system. We analyzed the possibility of using the host luminescence for two-color temperature sensing. The proposed method is improved by introducing the temporal dependence in the line intensity ratio measurements.